EXISTENTIALISM PERSPECTIVE: CAN CHARACTER EDUCATION OVERCOME THE PHENOMENON OF BULLYING IN SCHOOLS? - Lastiadi Muhtadin (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article is a literature review on the perspective of existentialism philosophy in the application of character education to overcome bullying in schools. Education is a process, not just the development of aspects of knowledge or just the transfer of knowledge from person to person, but also the process of transforming values (transfer of values) and building character in all its aspects. One of the trends in the flow of education that is developing is existentialism. This school has a certain view of "human freedom", the process of education, materials, and goals. Existentialism emphasizes the development of the individual as a whole. The relevance of the main teachings of existentialism philosophy to the goals of education in Indonesia lies in the basic value of existentialism to foster the affective domain with its elements which in turn can manifest behavior, reflecting the full picture of personality. The word existence is derived from the word "ex" which means exit, and "sistence" which is derived from the verb sisto (to stand, to place). Therefore, the word existence is defined: humans stand as themselves, by coming out of themselves.